Avaliação do mosto fermentativo de leveduras provenientes de cervejarias e otimização do processo de autólise industrial - Marcon, André (Universidade Federal de São Carlos, 2018)
Brewer's yeast, widely used in the fermentation industry, is an excellent source of protein, thus used by human and animal nutrition industries. Biomin Animal Nutrition of Brazil is an Austrian company that is renamed in the area of biotechnology, beginning its activities in 2008 in the city of Piracicaba - SP. Among its products is the autolysate yeast coming from the brewing process, acquired from large breweries in partnership with Biomin. This raw material can go through several fermentation cycles in the production companies, and these cycles can obviously cause interferences in the quality of this material. The detection of low levels of total protein in the final product (autolysed yeast), by Biomin, led to the interest of classifying the raw material from these breweries, in order to better understand its variables and how it can interfere with the process, also considering the steps of the standard treatment process of the raw material as well as the process of autolysis in a laboratory scale, in order to identify its flaws and promote optimization, aiming the quality improvement of the final product. The raw material was fully evaluated in the Biomin’s laboratories, where the parameters of pH, temperature, sensory (smell and color), dry matter content, cell viability, presence of residues, Brix level and the amount of protein, alcohol, acids and sugars were verified. It was found that there are small differences between the two main suppliers, mainly regarding alcohol, lactic acid, total protein present in the supernatant and cellular viability, being able to conclude that supplier "A" keeps better quality than "B" for physical-chemistry chacacteristics and higher viability too. However, generally speaking, the raw materials were considered to be of better quality than the expected before the experiments. There was also the analysis of the supplier "C" that contributed with different parameters from the two main suppliers. The knowledge of the nitrogenous content present in the in natura yeast (> 50 percentage) and its variation throughout the process was also recorded. As for the bench tests, which simulated the process of large-scale autolysis, it was possible to understand which stages were more harmful in the operation carried out in the company. Where, among them all, the most impacting was the exposure time of the yeast to the heating before centrifugation. Finally, by matching the understanding of the raw material characteristics to the better understanding of the stages of the process, it was possible to implement actions to a better handle of the raw material towards the desired final product and to define improvements for the production process.
Evaluation of the fermentative wort from breweries’ yeast and optimization of the industrial autolysis process
Keywords: Leveduras; Proteína bruta; Fermentação; Processo de autólise; Yeast; Total protein; Fermentation; Process of autolysis; Saccharomyces cerevisiae; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOQUIMICA DOS MICROORGANISMOS; CIENCIAS BIOLOGICAS::MICROBIOLOGIA